Breakfast Consumption Frequency and Its Relationships to Overall Diet Quality, Using Healthy Eating Index 2010, and Body Mass Index among Adolescents in a Low-Income Urban Setting. Issue 4 (4th July 2017) - Hopkins, Laura C.; Sattler, Melissa; Steeves, Elizabeth Anderson; Jones-Smith, Jessica C.; Gittelsohn, Joel
ABSTRACT: The aim of this study was to describe the relationship of breakfast frequency to diet quality and BMI among low-income, predominantly African American adolescents aged 9–15 (n = 239). Mean frequency of breakfast consumption was 5.0 ± 0.15 times per week. A significant, positive relationship was seen between HEI scores and frequency of breakfast consumption (p = .01). Dairy (p = .02) and whole grains (p < .01) HEI component scores were significantly related to breakfast frequency. No relationship was seen between breakfast frequency and BMI. Research with more rigorous designs should be conducted to assess the potential effects of breakfast consumption on diet quality in this population.